Excitation and propagation of X‐ray fluorescence through thin devices with hollowed ordered structures: comparison of experimental and theoretical spectra. (1st January 2016) - Mazuritskiy, M. I.; Dabagov, S. B.; Marcelli, A.; Lerer, A. M.; Dziedzic‐Kocurek, K.
Abstract : The lack of models describing the propagation of X‐rays in waveguides and the interference mechanism between incident and reflected radiation waves hamper the understanding and the control of wave propagation phenomena occurring in many real systems. Here, experimental spectra collected at the exit of microchannel plates (MCPs) under the total X‐ray reflection condition are presented. The results are discussed in the framework of a theoretical model in which the wave propagation is enhanced by the presence of a transition layer at the surface. The angular distributions of the propagating radiation at the exit of these MCPs with microchannels of ∼3 µm diameter will also be presented and discussed. These spectra show contributions associated with the reflection of the primary monochromatic beam and with the fluorescence radiation originating from the excitation of atoms composing the surface of the microchannel. The soft X‐ray fluorescence spectra collected at the exit of microcapillaries were analyzed in the framework of a wave approximation while diffraction contributions observed at the exit of these hollow X‐ray waveguides have been calculated using the Fraunhofer diffraction model for waves in the far‐field domain. Data collected at the Si L ‐edge show that in glassy MCPs the fluorescence radiation can be detected only when the energy of the primary monochromatic radiation is above the absorption edge for grazing angles higher than half of the critical angle of the total reflection phenomenon. Experimental data and simulations of the propagating radiation represent a clear experimental confirmation of the channeling phenomenon of the excited fluorescence radiation inside a medium and point out that a high transmission can be obtained in waveguide optics for parameters relevant to X‐ray imaging.